AB0026 DECREASE OF ANGIOGENIC T CELLS IN CONNECTIVE TISSUE DISEASE-ASSOCIATED INTERSTITIAL LUNG DISEASE - Pulito-Cueto, V.; Remuzgo Martinez, S.; Genre, F.; Atienza-Mateo, B.; Mora-Cuesta, V.M.; Iturbe-Fernández, D.; Lera-Gómez, L.; Pérez-Fernández, R.; Alonso Lecue, P.; Rodriguez Carrio, J.; Prieto-Peña, D.; Portilla, V.; et al. (Annals of the rheumatic diseases, 2021)
Interstitial lung disease (ILD) is one of the most significant complications of connective tissue diseases (CTD), leading to an increase of the morbidity and mortality in patients with CTD [1]. A specific T cell subset termed angiogenic T cells (TAng), that promote endothelial repair and revascularization, have been involved in the pathogenesis of CTD [2-4]. However, to the best of our knowledge, no information regarding the role of TAng in CTD-ILD+ is available. To study, for the first time, the potential role of TAng related to vascular damage in CTD-ILD+. Peripheral venous blood was collected from 40 patients with CTD-ILD+ and three comparative groups: 44 CTD-ILD- patients, 21 idiopathic pulmonary fibrosis (IPF) patients and 20 healthy controls (HC). All subjects were recruited from the Rheumatology and Pneumology departments of Hospital Universitario Marqués de Valdecilla, Santander, Spain. Quantification of TAng was performed by flow cytometry. TAng were considered as triple-positive for CD3, CD31 and CXCR4. Patients with CTD-ILD+ exhibited a significantly lower TAng frequency than CTD-ILD- patients (p<0.001). Similar results were obtained when patients with CTD-ILD+ were compared with HC (p=0.004) although no difference was observed between CTD-ILD+ and IPF. In addition, a significant increase of TAng frequency was shown in patients with CTD-ILD- in relation to IPF patients (p<0.001), while no difference was observed between CTD-ILD- and HC. Our results reveal a decrease of TAng frequency related to vascular damage in CTD-ILD+. Furthermore, we disclose that the presence of ILD is associated with lower TAng frequency. [1]Expert Rev Clin Immunol 2018;14(1):69-82. [2]Circulation 2007;116(15):1671-82. [3]Ann Rheum Dis 2015 74(5):921-7. [4]PLoS One 2017;12(8):e0183102. Personal funds, VP-C: PREVAL18/01 (IDIVAL); SR-M: RD16/0012/0009 (ISCIII-ERDF); LL-G: INNVAL20/06 (IDIVAL); RP-F: START PROJECT (FOREUM); RL-M: Miguel Servet type I CP16/00033 (ISCIII-ESF). Verónica Pulito-Cueto: None declared, Sara Remuzgo Martinez: None declared, Fernanda Genre: None declared, Belén Atienza-Mateo: None declared, Victor Manuel Mora-Cuesta: None declared, David Iturbe-Fernández: None declared, Leticia Lera-Gómez: None declared, Raquel Pérez-Fernández: None declared, Pilar Alonso Lecue: None declared, Javier Rodriguez Carrio: None declared, Diana Prieto-Peña: None declared, Virginia Portilla: None declared, Ricardo Blanco Speakers bureau: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen and MSD, Consultant of: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen and MSD, Grant/research support from: Abbvie, MSD and Roche, Alfonso Corrales: None declared, Jose Manuel Cifrián-Martínez: None declared, Raquel López-Mejías: None declared, Miguel A González-Gay Speakers bureau: Pfizer, Abbvie, MSD, Grant/research support from: Pfizer, Abbvie, MSD